Respostas

2014-05-29T13:10:32-03:00
a)x^2-2x+1=0

Δ = (-2)^2-4.1.1
Δ = 4-4
Δ = 0
Quando o delta é igual a zero, a equação há apenas uma raíz.

X =\frac{-(-2)+- \sqrt{0} }{2.1} =>X =  \frac{2+-0}{2} => X= \frac{2}{2} => X = 1

b) -x^2+5x-6=0

Δ = 5^2-4.(-1).(-6)
Δ = 25-24
Δ = 1

X =  \frac{-5+- \sqrt{1} }{2.(-1)} => X =  \frac{-5+-1}{-2}

x' =  \frac{-5+1}{-2} =>  \frac{-4}{-2} =2                           x" =  \frac{-5-1}{-2}=> \frac{-6}{-2} =3

c) x^2-2x+4=0

Δ = (-2)^2-4.1.4
Δ = 4-16
Δ = -12
Quando o delta é negativo, não há raíz!

Espero ter ajudado ;D

1 5 1